(untitled) (diségno, 2024)
The journal Rassegna. Problemi di architettura dell’ambiente (Review. Problems of the Architecture of the Environment), directed by Vittorio Gregotti and graphically edited by Pierluigi Cerri, was published from 1979 to 1999. Comprising 77 monographic numbers issued quarterly, each coordinated by influential cultural figures of the time, the periodical was developed during a historical period where the scientific, social, and professional worlds were preparing for the inexorable advent of the new millennium and the consequent phase of change on both the theoretical and practical levels. As the title implies, this editorial is a collection of considerations designed to enhance the understanding of the various architectural characters within significant macro themes. [read more]